The effect of Micro-arc Oxidation treatment on the microstructure and properties of open cell Ti6Al4V alloy foams - Korkmaz, Kemal (Elsevier Science Sa, 2015)
Micro-arc Oxidation is a widely used technique to produce thick, hard and strong adherent coatings on the transition metal surfaces. In the present study, Micro-arc Oxidation process was successfully applied to the open cell Ti6Al4V alloy foams which were manufactured by the use of the replication technique and powder metallurgy method. The morphology, microstructure and phase composition of the foam materials were investigated by XRD and SEM examinations. The coating is primarily composed of Al2TiO5, alpha-Al2O3 and gamma-Al2O3 phases. Additionally, mechanical properties of foam materials were characterized by compression tests which were performed on the samples. It is found out that the mechanical properties of the foam materials were significantly improved when compared to the untreated foam materials. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Micro-arc Oxidation; Coatings; Open cell; Metallic foams